Spatial Morphology Lab 01. International laboratory for comparative research in urban form. Street networks, Sweden - Motorised network of Eskilstuna - Stavroulaki, Ioanna; Berghauser Pont, Meta; Marcus, Lars; Sun, Kailun (Chalmers University of Technology, 2020)
GIS-datasets for the Street networks of Stockholm, Gothenburg and Eskilstuna produced as part of the Spatial Morphology Lab (SMoL).

The goal of the SMoL project is to develop a strong theory and methodology for urban planning & design research with an analytical approach. Three frequently recurring variables of spatial urban form are studied that together quite well capture and describe the central characteristics and qualities of the built environment: density, diversity and proximity.

The first measure describes how intensive a place can be used depending on how much built up area is found there. The second measure captures how differentiated the use of a place can be depending on the division in smaller units such as plots. The third measure describes how accessible a place is depending on how it relates with other places. Empirical studies have shown strong links between these metrics and people's use of cities such as pedestrian movement patterns.

To support this goal, a central objective of the project is the establishment of an international platform of GIS data models for comparative studies in spatial urban form comprising three European capitals: London in the UK, Amsterdam in the Netherlands and Stockholm in Sweden, as well as two additional Swedish cities of smaller size than Stockholm: Gothenburg and Eskilstuna.

The result of the project is a GIS database for the five cities covering the three basic layers of urban form: street network (motorised and non-motorised), buildings and plots systems.

The data is shared via SND to create a research infrastructure that is open to new study initiatives. The datasets for Amsterdam will also be uploaded to SND. The datasets of London cannot be uploaded because of licensing restrictions.

The street network GIS-maps include motorised and non-motorised networks. The motorised networks exclude all streets that are pedestrian-only and were cars are excluded. The network layers are based on the Swedish national road database, NVDB (Nationell Vägdatabas), downloaded from Trafikverket (https://lastkajen.trafikverket.se, date of download 15-5-2016, last update 8-11-2015). The original road-centre-line maps of all cities were edited based on the same basic representational principles and were converted into line-segment maps, using the following software: FME, Mapinfo professional and PST (Place Syntax Tool). The coordinate system is SWEREF99TM.
In the final line-segment maps (GIS-layers) all roads are represented with one line irrespectively of the number of lanes, except from Motorways and Highways which are represented with two lines, one for each direction, again irrespectively of the number of lanes. We followed the same editing and generalizing procedure for all maps aiming to remove errors and to increase comparability between networks. This process included removing duplicate and isolated lines, snapping and generalizing. The snapping threshold used was 2m (end points closer than 2m were snapped together). The generalizing threshold used was 1m (successive line segments with angular deviation less than 1m were merged into one). In the final editing step, all road polylines were segmented to their constituting line-segments. The aim was to create appropriate line-segment maps to be analysed using Angular Segment Analysis, a network centrality analysis method introduced in Space Syntax.

All network layers are complemented with an “Unlink points” layer; a GIS point layer with the locations of all non-level intersections, such as overpasses and underpasses, bridges, tunnels, flyovers and the like. The Unlink point layer is necessary to conduct network analysis that takes into account the non-planarity of the street network, using such software as PST (Place Syntax Tool).

GIS-databas för gatunätverk i Stockholm, Göteborg och Eskilstuna producerade som en del av Spatial Morphology Lab (SMoL).

Syftet med SMoL-projektet är att utveckla en stark teori och metod inom den arkitekturbaserade stadsbyggnadsforskningen med ett analytiskt tillvägagångssätt. Detta möjliggör kvantitativa
studier av grundläggande egenskaper hos den byggda miljön där relationer i rummet är centrala.

Det finns tre ofta återkommande begrepp med tillhörande mått som tillsammans ganska väl fångar och beskriver centrala egenskaper och kvaliteter hos stadens form: täthet, diversitet och närhet.

Förenklat kan man säga att det första måttet beskriver hur intensivt en plats är möjlig att använda beroende på hur mycket bebyggd yta som återfinns där. Det andra måttet fångar hur differentierad användningen av en plats kan vara beroende på hur indelad den är i flera rum. Det tredje måttet beskriver hur tillgänglig en plats är beroende på hur dess samband med andra platser är utformat. Empiriska studier har visat starka samband mellan dessa mått och människors användning av stadens rum i mycket grundläggande avseenden.

För att stödja detta syfte var projektets konkreta mål att upprätta en internationell plattform med GIS datamodeller för jämförande studier i rumslig stadsform som består av tre europeiska huvudstäder: London in England, Amsterdam i Nederländerna och Stockholm i Sverige, och två mindre svenska städer: Göteborg och Eskilstuna.

Resultat av projektet är en GIS-databas för de fem städerna som täcker de tre grundläggande lagren i stadsform: gatunätverk (motoriserade och icke-motoriserade), byggnader och fastigheter.

Denna data delas via SND för att skapa en forskningsinfrastruktur som är öppen för nya initiativ till studier. Data för Amsterdam kommer också att laddas upp till SND. Data för London kan inte delas på grund av licensbegränsningar.

Modellen för gatunätverket innehåller en modell som baseras på den motoriserade och en på den icke-motoriserade gatunätverk. De motoriserade modellen utesluter alla gator där bilar är uteslutna. Nätverkslagren är baserade på den svenska riksvägdatabasen, NVDB (Nationell Vägdatabas), nedladdad från Trafikverket (https://lastkajen.trafikverket.se, nedladdningsdatum 15-5-2016, senaste uppdatering 8-11-2015). De ursprungliga kartorna redigerades baserat på samma grundläggande representations-principer och omvandlades till linjesegmentskartor med användning av följande programvara: FME, Mapinfo professional och PST (Place Syntax Tool). Koordinatsystemet är SWEREF99TM.

I de finala linjesegmentkartorna är alla vägar representerade med en linje oberoende av antalet körfält, utom motorvägar som är representerade med två linjer, en för varje riktning, igen oberoende av antalet körfält. Vi följde samma redigerings- och generaliseringsförfarande för alla kartor som syftar till att öka jämförbarheten. Metodiken inkluderar att ta bort duplicerade och isolerade linjer, att koppla linjer där dem är felaktigt separerade och att generalisera modellen (dvs. använda samma detaljnivå). Vi använder tröskeln var 2 m (slutpunkterna närmare än 2 m knäpptes ihop). För generaliseringen används ett tröskelvärde av 1 m (successiva linjesegment med vinkelavvikelse mindre än 1 m slogs samman till ett). Sista steget är att segmentera alla linjer till deras konstituerande linjesegment. Analysen som används är ”Angular Segment Analys”, en metod som introducerats i Space Syntax.

Alla nätverks lager kompletteras med ett "Unlink points" -lager; ett lager som inkluderar alla icke-plankorsningar, t.ex. gångbroar och tunnlar. Unlinks är nödvändiga för att utföra nätverksanalys som tar hänsyn till gatunätets tredimensionella karaktär. Vi använder programvara PST (Place Syntax Tool) för redigeringen och analysen.

För mer detaljerad dokumentation, ladda ner dokumentationsfilen.
Spatial Morphology Lab 01. International laboratory for comparative research in urban form. Street networks, Sweden - Motoriserade gatunätverk, Eskilstuna
Keywords: URBAN AREAS; STADSOMRÅDEN; Spatial Analysis; Rumsanalys; spatial data file (GIS); spatial database (GIS); Administrative units; Administrativa enheter; Bio-geographical regions; Biogeografiska regioner; Coordinate reference systems; Referenskoordinatsystem; Transport networks; Transportnät; geospatial; geospatial; Engineering and Technology; Teknik; Civil Engineering; Samhällsbyggnadsteknik; Architectural Engineering; Arkitekturteknik; Infrastructure Engineering; Infrastrukturteknik; Transport Systems and Logistics; Transportteknik och logistik; Boundaries; Administrativa gränser; Structure; Byggnader och byggnadsanläggningar; Economy; Ekonomi; Geoscientific Information; Geovetenskap; Environment; Miljö; Location; Positionering; Society; Samhälle och kultur; Utilities / Communication; Tekniska försörjningssystem; Transportation; Transporter; Architecture; Arkitektur